2018
DOI: 10.1016/j.ab.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of potent and specific synthetic substrate for dipeptidyl-peptidase 7

Abstract: Bacterial dipeptidyl-peptidase (DPP) 7 liberates a dipeptide with a preference for aliphatic and aromatic penultimate residues from the N-terminus. Although synthetic substrates are useful for activity measurements, those currently used are problematic, because they are more efficiently degraded by DPP5. We here aimed to develop a potent and specific substrate and found that the k/K value for Phe-Met-methylcoumaryl-7-amide (MCA) (41.40 ± 0.83 μM s) was highest compared to Met-Leu-, Leu-Leu-, and Phe-Leu-MCA (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…3e). Preference for hydrophobic residues at the P2 position by SmDPP7 is in agreement with previous reports 21,24 . Nemoto et al reported that PgDPP7 and PgDPP11 exhibited a preference for hydrophobic amino acids at the P2 position of various dipeptidyl substrates and that the Phe664 (PgDPP7 numbering) is involved in the recognition of P2 hydrophobic amino acids 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3e). Preference for hydrophobic residues at the P2 position by SmDPP7 is in agreement with previous reports 21,24 . Nemoto et al reported that PgDPP7 and PgDPP11 exhibited a preference for hydrophobic amino acids at the P2 position of various dipeptidyl substrates and that the Phe664 (PgDPP7 numbering) is involved in the recognition of P2 hydrophobic amino acids 21 .…”
Section: Discussionsupporting
confidence: 93%
“…SmDPP7 showed clear preferences for hydrophobic and basic amino acids at the P1 position. This result was in agreement with previous reports, in which PmDAP BII and PgDPP7 showed substrate P1 preferences against hydrophobic and basic amino acids 11,24 . In order to quantitatively estimate the substrate preference at the P2 position, inhibitory effects of the dipeptides Xaa-Tyr against the hydrolytic activity of wild-type SmDPP7 were evaluated on a synthetic substrate, tyrosyl-L-tyrosine 4methylcoumaryl-7-amide (Tyr-Tyr-MCA).…”
Section: P2 Position Preferences Of Smdpp7supporting
confidence: 94%
“…In this respect, it should be noted that human DPP7 is not related to bacterial DPP7, but rather is an isozyme of DPP2 (Bezerra et al, 2012). DPP7 releases the N-terminal dipeptide NH 2 -Xaa1-Zaa2 (Zaa, hydrophobic residues) (Banbula et al, 2001;, and hydrolyzes insulin B chain, type I collagen, and azocasein in vitro (Banbula et al, 2001) Since the P1-position specificity of DPP7 overlaps with that of DPP5, findings of a specific synthetic substrate for DPP7 were eagerly anticipated and Phe-Met-MCA finally identified (Nemoto et al, 2018).…”
Section: Dpp7mentioning
confidence: 99%
“…In this respect, it should be noted that human DPP7 is not related to bacterial DPP7, but rather is an isozyme of DPP2 (Bezerra et al., 2012). DPP7 releases the N‐terminal dipeptide NH 2 ‐Xaa1‐Zaa2 (Zaa, hydrophobic residues) (Banbula et al., 2001; Rouf, et al., 2013), and hydrolyzes insulin B chain, type I collagen, and azocasein in vitro (Banbula et al., 2001) Since the P1‐position specificity of DPP7 overlaps with that of DPP5, findings of a specific synthetic substrate for DPP7 were eagerly anticipated and Phe‐Met‐MCA finally identified (Nemoto et al., 2018). As a result, it is now possible to distinctly measure all DPP activities expressed in bacteria and clinical specimens with Arg‐Arg‐, Gly‐Pro‐, Lys‐Ala‐, Phe‐Met‐, and Leu‐Asp‐MCA for DPP3, DPP4, DPP5, DPP7, and DPP11, respectively, as well as for determining activities in saliva and subgingival dental plaque specimens.…”
Section: Degradation Of Extracellular Proteins Initiated By Gingipainsmentioning
confidence: 99%
“…The activity of DPP7 is scarcely distinguishable from that of DPP5 due to their similar hydrophobic P1-position preferences. However, a recent investigation of P2-and P1-position specificities established Phe-Met-MCA as a novel DPP7 specific substrate (Nemoto, Ohara-Nemoto, and Ono 2018). Consequently, these four different dipeptidyl substrates allow for quantitative measurements of the activities of the four known DPPs in bacterial cells as well as human specimens.…”
Section: Introductionmentioning
confidence: 99%